Comparison of 4-hydroxynonenal induced p53-mediated apoptosis in prostate cancer cells LNCaP and DU145 - Cao, Zhi-gang; Xu, Xu; Xue, Ye-Min; Zhao, Shu-Li (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: To explore the mechanism of oxidative stress in the development of prostate cancer, here we compared 4-hydroxynonenal (4-HNE)- treated LNCaP (hormone-sensitive) and DU145 (hormone insensitive) cells with significant differences in sensitivity to androgen. Material and methods: The prostate cancer cell line LNCaP and late cell line DU145 were treated with different concentrations of 4-HNE. The cell proliferation, apoptosis and mitochondrial transmembrane potential were detected at different time points, and expression of related molecules in cell proliferation and apoptosis signal pathway was analyzed by Western blot, and the over-expression of glutathione S-transferase (GSTA-4) was used to validate the changes of the effects of 4-HNE on the two kinds of cells. Results: LNCaP cells showed greater antiproliferative and proapoptotic activities of HNE in a time- and dose-dependent manner corresponding to the activation of p53-mediated intrinsic apoptotic signaling, but JNK activation was not observed. In contrast, HNE-treated DU145 cells showed less apoptosis and proliferation was not inhibited; instead there was sustained activation of JNK, but activation of p53, p-p53, p21, Bax and caspase-3 was not observed. In addition, their effect of induction of apoptosis can be inhibited by overexpression of GSTA-4. Conclusions : These studies suggest that 4-HNE promotes prostate cancer cell apoptosis through the p53 signaling pathway; the differences of sensitivity to 4-HNE in LNCaP and DU145 cells may be related to the androgen sensitivity of prostate cancer cells; and the 4-HNE-induced p53-mediated apoptosis signal is regulated by GSTA-4.